علم العروض وتدريسه: تجربة في الجامعة الإسلامية العالمية بماليزيا - Teaching Arabic prosody: an exploration study at International Islamic University Malaysia (IIUM) - Ahmad Safian, Nursafira (PIMM Experts SDN BHD, 2019)
ملخص البحث: تتناول هذه الدراسة تجربة الباحثة في تدريس علم العروض في الجامعة الإسلامية العالمية بماليزيا. وقد استعانت الباحثة بالأنغام الموسيقية في تدريس علم العروض؛ نظرا لتوافر العلاقة القوية بين هذا العلم والموسيقى، فضلا عن أنه يعنى بدراسة موسيقى الشعر العربي وإيقاعاته. ومن الأهداف العامة من دراسة علم العروض قدرة الدارسين على تقطيع الشعر العربي وقراءته قراءة صحيحة مع مراعاة أوزان البحور الشعرية. وعلى الرغم من ذلك، وجد كثير من الطلاب الملايويين المتخصصين في اللغة العربية في الجامعة الإسلامية العالمية بماليزيا يواجهون صعوبة في الإقبال على دراسة علم العروض، بل إن بعضهم ينفر منها؛ نظرا لعدم استطاعته أن ينسب بيتا من الأشعار إلى بحره. وانطلاقا من هذا الصدد، لجأت الباحثة إلى توظيف إيقاعات الفنّان الملايوي (بي.رملي) الموسيقية في علم العروض. وتهدف هذه الدراسة إلى إعانة هؤلاء الطلاب في تعلّم العروض بشكل ميسّر جنبا إلى جنب أنها تسهم في إظهار إبداعية (بي.رملي) في صياغة إيقاعاته الموسيقية. وتعتمد الباحثة في هذه الدراسة على منهج الوصف؛ إذ تقوم في بداية الدراسة بالعرض عن الوضع العام لعلم العروض في قسم اللغة العربية وآدابها بكلية معارف الوحي والعلوم الإنسانية في الجامعة الإسلامية العالمية بماليزيا، كما أنها تقوم بوصف طرق التدريس المتبعة لتعلّم علم العروض في هذه الجامعة، إضافة إلى إبراز أنغام (بي. رملي) الموسيقية المناسبة للبحور الشعرية. ومما توصلت إليه الباحثة من خلال هذه الدراسة أن إيقاعات (بي. رملي) الموسيقية المستخدمة في أفلامه الغزيرة تصلح أن تكون أداة من الأدوات التعليمية المساعدة لدراسة علم العروض، منها: "أجي أجي بوكا فينتو"، و"هاي أوبات هاي أوبات"، وغيرهما كثير، بل أصبحت دراسة العروض مادة حية تطبيقية، يمكن استشعار حلاوتها لدى الطلاب الناطقين بغير العربية. ************************************************************************** This study exposed the experiences of researcher in teaching Arabic prosody at International Islamic University Malaysia (IIUM), by using melodies as a method of teaching; since there are correlation between Arabic prosody and melodies. The objectives of learning Arabic prosody is to assist the students to recite Arabic poems with sound understanding and to help them identify perfect poetic meters from the defective and to distinguish between their various kinds. Nevertheless, most of the students who specialized in Arabic language and literature at IIUM have difficulty in learning this course, even some of them did not engage with the lesson seriously; as they do not know how to distinguish between the various kinds of meters. Therefore, the researcher suggested to use the melodies of prominent and versatile Malay star, P.Ramlee in learning Arabic prosody. This study aims to assist the students in learning Arabic prosody by using easy approaches as well as to identify the creativity of P.Ramlee in constructing his melodies. The design of this research is a descriptive study, in which the researcher explained generally about Arabic prosody that being taught at Department of Arabic Language and Literature, Kulliyyah of Islamic Revealed Knowledge and Human Sciences, IIUM. The researcher revealed the methods of teaching that are being used in learning Arabic prosody, and also described some of melodies of P.Ramlee which are suitable to the Arabic poetic meters. The finding of research showed that the P.Ramlee’s melodies from his abundant films, are useful for educational teaching materials especially in learning Arabic prosody, for instance, the rhythm entitled “Aci aci buka pintu”, “Hai ubat hai ubat” and etc. By using this method, the students paid more attention in learning Arabic prosody, hence they could understand the course in an effective way.